Strategic Processes in Georgian Manufacturing Companies – Business-Level Strategy Perspective - Khoshtaria, Tornike (Management and Administration Journal, 2019)
The purpose of this study is to examine the links between generic strategy types and organizational performance. Moreover, this paper will attempt to discover whether or not the emphasis on planning strategy implementation will enhance a company with superior performance. This paper studied 104 Georgian based manufacturing companies. A questionnaire was chosen as the survey instrument. The respondents selected were CEOs of the manufacturing companies being surveyed. Findings of this study are based on the results of the hypotheses tests which indicate that companies with clearly defined business strategies are performing better. The group of companies with integrated strategies had better performance than those concentrating on either of them. This contradicts the idea that it is not effective to use a combination of cost-leadership and differentiation strategy because of their exclusivity. There were no strong ties established between the strategic type and the planning of strategic implementation. Moreover, companies placing emphasis on planning strategy implementation have better performances than those “stuck in the middle”. The results of this study are particularly useful for practitioners, as it can provide managers with the information connected with strategy formulation and implementation processes. This study makes a contribution to the existing literature by exploring strategy processes within Georgian based manufacturing companies, and addressing the inconclusiveness of the results of generic strategies and organizational performance.